2021
DOI: 10.31314/mjk.10.1.9-16.2021
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor-Faktor Yang Mempengaruhi Pemberian ASI Ekslusif Pada Bayi Di Puskesmas Talaga Jaya

Abstract: Exclusive breastfeeding is breastfeeding for 6 months without providing complementary foods or drinks. The health center with the lowest achievement of exclusive breastfeeding, based on data from the Gorontalo Provincial Health Office, is the Talaga Jaya Health Center. The purpose of this study was to determine the factors that influence exclusive breastfeeding for infants at the Talaga Jaya Health Center. This research is a quantitative research. The population is all infants aged 7-11 months totaling 290 peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Research that conducted by Adityaningrum, et al (2021), regarding the Analysis of Factors Affecting Exclusive Breastfeeding for Babies at the Talaga Jaya Health Center, it was found that the mother's education, mother's occupation, implementation of IMD and family support obtained a p-value (0.000) less than (0 0.05), while the support of health workers has a p-value (0.998) more than (0.05).…”
Section: Distribution Of the Frequency Of Work Of Mothers In The Krui...mentioning
confidence: 98%
See 1 more Smart Citation
“…Research that conducted by Adityaningrum, et al (2021), regarding the Analysis of Factors Affecting Exclusive Breastfeeding for Babies at the Talaga Jaya Health Center, it was found that the mother's education, mother's occupation, implementation of IMD and family support obtained a p-value (0.000) less than (0 0.05), while the support of health workers has a p-value (0.998) more than (0.05).…”
Section: Distribution Of the Frequency Of Work Of Mothers In The Krui...mentioning
confidence: 98%
“…Research conducted by Adityaningrum, et al (2021), regarding the Analysis of Factors Affecting Exclusive Breastfeeding for Babies at the Talaga Jaya Health Center, it was found that the mother's education, mother's occupation, implementation of IMD and family support obtained a p-value (0.000) less than (0.05), while the support of health workers has a p-value (0.998) more than (0.05). The factors that influence exclusive breastfeeding for infants at the Talaga Jaya Health Center are mother's education, mother's occupation, implementation of IMD, and family support.…”
Section: Bivariate Analysismentioning
confidence: 99%
“…Akan tetapi, beberapa provinsi masih belum mencapai target, salah satunya Provinsi Gorontalo yang hanya mencapai 43,35% dan berada di urutan ketiga terendah. Bahkan di Kabupaten Gorontalo pada tahun 2020, berdasarkan data Dinas Kesehatan Provinsi Gorontalo, mengalami penurunan dan berada diurutan pertama terendah yaitu sebesar 11,30%, sebelumnya tahun 2019 sebesar 45,35% (Adityaningrum et al, 2021). Rendahnya cakupan pemberian ASI disebabkan oleh beberapa hambatan yang dapat menjadi kegagalan tercapainya pemberian ASI.…”
unclassified